Changes in the Price Policy of the Trading Company as a Result of the Global Economic Crisis After Covid-19 and the War in Ukraine - Dikova, Iliyana (Research Papers, 2023)
In the conditions of changes in the economic situation, which led to inflation, trade companies are put to the test of transforming their pricing strategy and at the same time remaining competitive on the goods market. Rising resource prices lead to significant increases in inflation rates internationally. Those who offer goods to their consumers must take a position for a longer-term and sustainable change in their pricing strategy, so that they generate a profit with which they manage to cover the costs of producing or selling their products. In addition to changes in profit management, it will be necessary to include marketing methods to promote products and inform customers about their qualities. Increasing the market share of the companies will not be the only goal if they desire the long-term of their business, but they will have to create strategies to increase their revenue without it being dependent on the volume of sales.
Keywords: Sales; Price strategy; Inflation; Profit; Competitiveness; Cost